Bispecific Antibody-Bound T Cells as a Novel Anticancer Immunotherapy - Cho, Jaewon; Tae, Nara; Ahn, Jae Hee; Chang, Sun Young; Ko, Hyun Jeong; Kim, Dae Hee (Biomolecules and Therapeutics, 2022)
Chimeric antigen receptor T (CAR-T) cell therapy is one of the promising anticancer treatments. It shows a high overall response rate with complete response to blood cancer. However, there is a limitation to solid tumor treatment. Additionally, this currently approved therapy exhibits side effects such as cytokine release syndrome and neurotoxicity. Alternatively, bispecific antibody is an innovative therapeutic tool that simultaneously engages specific immune cells to disease-related target cells. Since programmed death ligand 1 (PD-L1) is an immune checkpoint molecule highly expressed in some cancer cells, in the current study, we generated αCD3xαPD-L1 bispecific antibody (BiTE) which can engage T cells to PD-L1+ cancer cells. We observed that the BiTE-bound OT-1 T cells effectively killed cancer cells in vitro and in vivo. They substantially increased the recruitment of effector memory CD8+ T cells having CD8+CD44+CD62Llow phenotype in tumor. Interestingly, we also observed that BiTE-bound polyclonal T cells showed highly efficacious tumor killing activity in vivo in comparison with the direct intravenous treatment of bispecific antibody, suggesting that PD-L1-directed migration and engagement of activated T cells might increase cancer cell killing. Additionally, BiTE-bound CAR-T cells which targets human Her-2/neu exhibited enhanced killing effect on Her-2-expressing cancer cells in vivo, suggesting that this could be a novel therapeutic regimen. Collectively, our results suggested that engaging activated T cells with cancer cells using αCD3xαPD-L1 BiTE could be an innovative next generation anticancer therapy which exerts simultaneous inhibitory functions on PD-L1 as well as increasing the infiltration of activated T cells having effector memory phenotype in tumor site.
Keywords: Anticancer immunotherapy; Bispecific antibody; Bispecific T cell engager; CAR-T; PD-L1